A Low Embodied Energy Approach for Early Design Decisions in Agritourism Centers in Pune - Kashish Dewani (International Journal of Rural and Regional Development, 2025)
Agritourism is an idea that empowers and trains the rural family, organization, or individual to generate alternative sources of income by transforming their traditional agricultural land into a tourist attraction. Agritourism is the practice of attracting visitors to an area used primarily for agricultural purposes. It could be described as – rural/agricultural environments + farm commodities + tourism services = agritourism. It gives visitors an experience to stay in a countryside setting and experience firsthand the production processes of their own food! Agritourism settings are established in a village, in close proximity to farmers, making it easy for them to manage the activities. However, being away from cities puts challenges for maintenance in terms of resource utilization as well. This is where energy efficiency becomes urgent. In Maharashtra, there has been a significant increase in agritourism initiatives that attract city residents looking to reestablish a connection with the environment and help boost rural economies. Nonetheless, obstacles like remote areas, scarce resource control, and infrastructure deficiencies highlight the importance of implementing sustainable, energy-efficient strategies in agritourism projects to guarantee the lasting success of nearby populations. The concept of agritourism should focus on minimized energy during planning, construction and operation ensuring its financial viability for farmers. But 60% to 80% of energy consumed by a building is the energy required to manufacture the building materials. High initial embodied energy building materials showcase extensive energy for extraction, manufacturing, processing, and transportation leading to higher carbon emission, whereas, materials with lower initial embodied energy, not only exhibit reduced energy consumption during its manufacturing stages, but often demonstrate superior thermal performance, resulting in reduced operational costs and environmental impact as well. So, to address this challenge, a holistic approach is required that takes into account the life cycle of building material from its manufacture to disposal, also considering its source, nature, recyclability, and environmental impact. The study follows a literature-based approach to put forward the design strategies for the agritourism center concerning building materials within the scope of architecture, in the context of a site situated in Gohe Bk. village, Pune district, Maharashtra and supports Maharashtra's agritourism policies, which promote the use of energy efficient and low carbon footprint building material in agritourism infrastructure development.
Keywords: Agritourism; Embodied energy; Maharashtra; Materials; Pune; carbon footprint